Bacterial cellulose: a versatile biopolymer for wound dressing applications - Portela, Raquel (2019)
This work is funded by FEDER funds through the COMPETE 2020 Program, and National Funds through FCT - Portuguese Foundation for Science and Technology under the projects: POCI-01-0145-FEDER-007688 (Reference UID/CTM/50025/2013), UID/Multi/04378/2019 (Unidade de Ci<^> encias Biomoleculares Aplicadas - UCIBIO) and co-financed by FEDER funds through PT2020 Partnership Agreement (POCI-01-0145-FEDER-07728); PTDC/FIS-NAN/0117/2014; and PTDC/BIA-MIC/31645/2017.